Lightweight pneumatic semi-universal hand with two fingers aimed for a wide range of grasping. (17th December 2017) - Dameitry, Ashlih; Tsukagoshi, Hideyuki
Abstract: This paper presents the design and implementation of a semi-universal robot hand with lightweight structure capable of grasping various shapes of objects. Taking inspiration from human grasping capability, we introduce a new two-fingered grasping taxonomy with semi-adducted thumb position criterion. Based on it, we propose a sensor-less two finger hand with 3-DOF structure formed by a thumb and an index finger. We also introduce a novel pneumatic actuator composed of a pleated flat tube and the notch structure, which enables the joints to generate larger torque and wider workspace than conventional actuators with the similar weight. Besides, the symmetrical driving motion, in which IP and MCP joints in symmetric position are connected as the same chamber, is introduced to reduce the number of degrees without degrading the performance. Then, we demonstrate the success rate for grasping various objects by the developed prototype. The experimental results suggest us the validity of our proposed method, and its effectiveness is discussed after comparing with the previously developed robot hands. Abstract :